Stereoselective synthesis of (-)-microcarpalide - Chavan, Subhash P.; Praveen, C. (Tetrahedron Letters, 2005)
A highly convergent and efficient synthesis of (-)-microcarpalide, a 10-membered lactone displaying remarkable microfilament disrupting activity is described. Ring-closing metathesis and Sharpless asymmetric dihydroxylations are the key steps. Our strategy highlights the application of novel hydroxy lactone precursors for the stereoselective synthesis of (-)-microcarpalide. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: 4-diol; cis-2-butene-1; Claisen ortho ester rearrangement; microcarpalide; Ring-closing metathesis; sharpless asymmetric dihydroxylation